Portuguese coffee: is there a concern regarding mycotoxins contamination? - Viegas, Susana (2017)
According to the International Coffee Organization, global coffee production is rising driven by an increase in total demand. However, similar to other crops, coffee cherries, and beans are exposed to contamination and consequent colonization by fungi during different phases of plant development, harvesting, transport, and storage. Consequently, mycotoxins also contaminate coffee beans although the roasting process has an important role in reducing mycotoxins presence, depending upon the combination of time and temperature. Since each country applies different roasting conditions, significant differences in mycotoxins concentrations occur across Europe with respect to contamination levels even when the origin of the coffee is the same. A previous paper showed high contamination by toxigenic mycobiota of coffee beans to be used in Portuguese coffee industries.